Pemanfaatan Instagram sebagai Media Dakwah bagi Mahasiswa Program Studi Manajemen Dakwah - Oktavia, Vina; Depi Putri; Elce Purwandari; Artiyanto (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze the forms of da’wah content disseminated by students, their level of participation in content production, and the role of digital literacy in supporting da’wah activities through social media. This research employs a qualitative approach using a case study method, with in-depth interviews conducted with active students, alumni, and lecturers within the Islamic Preaching Management Study Program at Universitas Islam Nusantara Al-Azhaar Lubuklinggau. The findings indicate that Instagram is actively utilized as a platform for da’wah, featuring various content formats such as short videos, Qur’anic verses, hadith quotations, and Islamic motivational messages presented in an engaging and youth-oriented manner. Students demonstrate a high level of enthusiasm in producing da’wah content; however, they still face several challenges, including limited technical skills in content creation, inconsistency in account management, and insufficient institutional support. Despite these challenges, digital da’wah through Instagram has proven to be effective in reaching a broad youth audience and aligning with contemporary digital communication patterns. In conclusion, Instagram holds significant potential as a strategic medium for contemporary da’wah; however, its effectiveness is highly dependent on the enhancement of digital literacy, student creativity, and sustained institutional support. Keywords: Digital Da’wah, Instagram, Student Engagement.